2002
DOI: 10.1159/000067207
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Endothelial Implants Inhibit Intimal Hyperplasia in a Model of Arteriovenous Fistulae: A Safety and Efficacy Study in the Pig

Abstract: Vascular access complications are a major problem in hemodialysis patients. Native arteriovenous fistulae, historically the preferred mode of access, have a patency rate of only 60% at 1 year. The most common mode of failure is due to progressive stenosis at the anastomotic site. We have previously demonstrated that perivascular endothelial cell implants inhibit intimal thickening following acute balloon injury in pigs and now seek to determine if these implants provide a similar benefit in the chronic and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
3

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 18 publications
0
49
0
Order By: Relevance
“…Endothelial cells (ECs) embedded within a 3D denatured collagen matrix secrete antiproliferative, antithrombotic, and antiinflammatory agents that promote vascular repair even when such constructs are placed far from the lumen within the vascular adventitia. Luminal inflammation, occlusive thrombosis, and intimal hyperplasia can be controlled by allo-and xenogeneic matrix-embedded (ME) ECs in a manner indistinct from native endothelium and without eliciting a significant immune response (1)(2)(3)(4)(5)(6)(7)(8). The challenge posed is whether endothelial implants recapitulate the endothelium lining as an epithelium or add to the regulation by perfusing vessels of the vasa vasorum, which are principally comprised of ECs.…”
mentioning
confidence: 99%
“…Endothelial cells (ECs) embedded within a 3D denatured collagen matrix secrete antiproliferative, antithrombotic, and antiinflammatory agents that promote vascular repair even when such constructs are placed far from the lumen within the vascular adventitia. Luminal inflammation, occlusive thrombosis, and intimal hyperplasia can be controlled by allo-and xenogeneic matrix-embedded (ME) ECs in a manner indistinct from native endothelium and without eliciting a significant immune response (1)(2)(3)(4)(5)(6)(7)(8). The challenge posed is whether endothelial implants recapitulate the endothelium lining as an epithelium or add to the regulation by perfusing vessels of the vasa vasorum, which are principally comprised of ECs.…”
mentioning
confidence: 99%
“…Side-to-side arteriovenous fistulae were created with femoral arteries and veins in pigs. 74 Intimal thickening, observed within the venous segment at 1 and 2 months, was significantly reduced in the EC-treated animals compared with control animals.…”
Section: Te Perivascular Implantsmentioning
confidence: 85%
“…Once it was shown that paracrine-mediated regulation is disrupted in injury to the native endothelium [14][15][16], it was further suggested that implants containing healthy donor endothelial cells could restore the host intrinsic regulatory power and induce normal vascular repair [17][18][19][20][21][22]. Denatured collagen matrices that promoted endothelial cell attachment and regulatory phenotype were used to matrixembed endothelial cells [23].…”
Section: The Development Of Endothelial Cell-based Paracrine Tissmentioning
confidence: 99%